2020
DOI: 10.1136/bmjopen-2019-035508
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial assessing the effect of a technology-assisted gait and balance training on mobility in older people after hip fracture: study protocol

Abstract: IntroductionDeficits in balance and walking ability are relevant risk factors for falls during ageing. Moreover, falls are a risk factor for future falls, strongly associated with adverse health outcomes, such as fear of falling or fractures, particularly, hip fracture. For this reason, the development of prevention tools and innovative rehabilitation strategies is one of the main objectives in geriatrics. Effective interventions to promote hip recovery after hip fracture are characterised by intensive and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…While the focus of common rehabilitative approaches for patients with PD relies on the improvement of static and dynamic balance, walking, and falls (50)(51)(52). It was recently found that performance improvements after technology-delivered balance training correlate with evident neurobiological changes in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…While the focus of common rehabilitative approaches for patients with PD relies on the improvement of static and dynamic balance, walking, and falls (50)(51)(52). It was recently found that performance improvements after technology-delivered balance training correlate with evident neurobiological changes in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Gait function. The walking function of the 2 groups of patients was collected before and after treatment, and the walking speed (WS) and stride length (SL) of the lower extremities were evaluated using the digital treadmill Tecno Body Walker-view (Bergamo, Bergamo, Italy) ( 28 ). Tecno Body Medical Fitness Software (version number: 2.7.8.0) was used to process the collected data and obtain WS and SL, taking 3 repeated measurements, from which the mean was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Fractures occurring in the proximal femur can be transformative experiences for elderly individuals and are frequently linked to a significantly higher risk of mortality. The management of these fractures involves a standardized diagnostic and therapeutic algorithm to minimize complications and optimize resources [11,12].…”
Section: Introductionmentioning
confidence: 99%